Force and impedance control for hydraulically driven hexapod robot walking on uneven terrain - Addie Irawan, Hashim (2012)
A variety approach of multi-legged robot designs, especially on a large scale design with hydraulically driven actuators exist, but most of it still unsolved and used primitive techniques on control solutions. This made this area of research still far from demonstrating the scientific solutions, which is more towards developing and optimizing the algorithm, control technique and software engineering for practical locomotion (flexibility and reliability). Therefore in this thesis,the study is done to propose two categories of solution for statically stable and hydraulically driven hexapod robot, named COMET-IV, which are dynamic walking trajectory generation and force/impedance control implementation (during body start patching), in order to solve the stability problems (horizontal) that encountered when walking on extremely uneven terrains.Only three sensors are used for control feedback; potentiometers (each leg joint), pressure sensors (hydraulic cylinders) and attitude sensor (center of body). For dynamic walking trajectory generation, the fixed/determined of tripod walking trajectory is modified with force threshold-based, named as environment trailed trajectory (ETT),on each first step of foot during support phase (preliminary sensing uneven terrain surfaces). Moreover,the proposed dynamic trajectory generation is then upgraded with capability of omni-directional walking with a proposed center of body rotational-based method. The instability of using the ETT module alone and with proposed hybrid force/position control in the previous progress, during body patching on walking session is then solved using the proposed pull-back position-based force control (PPF). PPF controller is derived from the ETT module itself and supported by proposed compliant (switching) mechanism, logical attitude control and dynamic swing rising control. The limitation of PPF controller applied with ETT module for walking on uneven terrain contains extreme soft surface makes the study narrowed to the impedance control approaches as a replacement of PPF controller. Three new adaptive impedance controller are designed and proposed: Optimal single leg impedance control based on body inertia, Optimal center of mass—based impedance control based on body inertia and Single leg impedance control with self-tuning stiffness. To reduce the hard swinging/shaking of the robot's body in motion that arise after applying the proposed impedance controllers, fuzzy logic control via Takagaki-Sugeno-Kang (TSK) model is proposed to be cascaded on the input feedback of the controller.The study has verified the effectiveness of both categories of control unit (dynamic trajectory,force controller and impedance controllers) combination throughout several experiments of COMET-IV walking on uneven/unstructured terrains.